Self-color-changing bio-based photonic crystal coating and application thereof
By using photon coatings prepared by cellulose nanocrystals and other chemical substances, the contamination and immutability of existing photonic crystal materials in food safety detection are solved, and a photon coating with high flexibility and self-discoloration characteristics is achieved, which is suitable for humidity detection of food packaging.
Patent Information
- Application Number
- CN202411858391.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
In environmental monitoring, existing photonic crystal materials have problems such as contamination, difficulty in contact with food, complicated degradation and low recycling rate, and difficult to change the structural color control, which limits their application in food safety testing.
Cellulose nanocrystals are used as biological raw materials for structural color development, and cellulose nanocrystals are prepared by traditional sulfuric acid method, and mixed with acrylamide, acrylic acid, crosslinking agent and photoinitiator. After rotary evaporation concentration and ultraviolet photopolymerization, a high flexibility and self-discoloration photonic coating is prepared.
It realizes the high flexibility and self-discoloration characteristics of photon coatings, can quickly self-discoloration under different humidity environments, is suitable for humidity detection in the food packaging field, and has good biocompatibility and degradability.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of photonic coatings, and in particular relates to a self-coloring bio-based photonic crystal coating and application thereof. Background Art
[0002] With the advancement of micro-nanotechnology, structural colors generated by highly ordered microstructures using the principle of bionic color development have been widely used in optical coating materials. As the most intuitive way of observation, color has unique advantages in environmental monitoring. Therefore, it is very necessary to use structural colors to build new visual detection products. At present, bionic structural colors mainly come from building photonic crystal structures. The most common method on the market is to control the particle size of monodisperse polymer microspheres (such as polystyrene microspheres, polymethyl methacrylate microspheres, silica microspheres, etc.) to regulate the color presented by photonic crystals. However, this type of material for preparing photonic crystals often pollutes the environment to a certain extent: on the one hand, this type of material is not easy to be used in food safety, and it is even more difficult to come into direct contact with food; on the other hand, the degradation process of this type of material is cumbersome and the recycling rate is low. In addition, the regulation of structural colors constructed by microspheres generally regulates the particle size during preparation, and it is difficult to change its own color after finalization, which is not conducive to intuitive (naked eye observation) environmental detection.
[0003] In order to effectively solve the above drawbacks, the key is to use biomaterials as raw materials for structural color. At present, cellulose nanocrystals are the main biological raw materials for constructing structural colors. However, structural color materials based on cellulose nanocrystals are mainly in the form of films, and their shortcomings, such as high brittleness, long environmental sensing time, and difficulty in adhesion, make them difficult to apply in the field of photonic coatings, especially in the field of photonic packaging coatings. Summary of the invention
[0004] In order to overcome the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a self-coloring bio-based photonic crystal coating and its application. The present invention is divided into two steps: first, a cellulose nanocrystal composite system is introduced into an ethanol system to prepare a photonic coating that can quickly concentrate and color; then, the photonic coating is photopolymerized to prepare a highly flexible and self-coloring photonic coating material. The photonic coating material of the present invention is used in the fields of visualized photonic packaging coatings and the like.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a self-coloring bio-based photonic crystal coating comprises the following steps:
[0007] (1) Cellulose nanocrystals were prepared by the conventional sulfuric acid method, except for the centrifugal washing step: the acid was replaced by water during the first two room temperature centrifugal washings and by ethanol during the last two low temperature centrifugal washings, ultimately obtaining a cellulose / ethanol / water mixture.
[0008] The concentration of the ethanol is 95%, and the solvent is water; the preparation method of cellulose nanocrystals is the traditional sulfuric acid method (i.e., 64% concentrated sulfuric acid is used to treat wood pulp at 50°C for 40 minutes, and then centrifuged to achieve the purpose of cleaning and concentration), the acid hydrolysis raw materials are wood pulp, cotton pulp, and straw pulp, preferably wood pulp; the number of centrifugation is 4 times, and the low-temperature centrifugation temperature is 5°C; the volume ratio of ethanol and water in the cellulose nanocrystal / ethanol / water mixture is 4-6:6-4, and the concentration of the cellulose nanocrystal mixture is 2.5-3wt%.
[0009] (2) The mixed solution obtained in step (1) is then mixed with acrylamide, acrylic acid, a crosslinking agent and a photoinitiator to obtain a mixed solution. The molar mixing ratio of acrylamide and acrylic acid is 3-4:1, and the amount of the crosslinking agent and the photoinitiator added is 0.3% of the molar mass of acrylamide; the crosslinking agent is methylenebisacrylamide, hydroxymethylpropane trimethylene ester, etc., preferably methylenebisacrylamide; the photoinitiator type is photoinitiator 651, photoinitiator TPO, photoinitiator 2959, etc., preferably 2959. The amount of the mixed solution of acrylamide, acrylic acid, methylenebisacrylamide and photoinitiator 2959 added is 20-40wt% of the mixed solution of step (1).
[0010] (3) The mixed solution obtained in step (2) is concentrated by rotary evaporation at a certain temperature to obtain a photon coating containing acrylamide, acrylic acid, a crosslinking agent and a photoinitiator. The rotary evaporation volume of the mixed solution is 200-300 ml, the rotary evaporation concentration temperature is 30° C., and the rotary evaporation time is 5-30 min. The concentration of the photon coating is 4-8 wt %.
[0011] (4) subjecting the photon coating obtained in step (3) to ultraviolet polymerization to obtain a photon coating with high toughness and self-coloring. The ultraviolet polymerization is irradiated at 365nm and the polymerization time is 20-30min. The thickness of the photon coating is 80-120um. The characteristic is that during this process, the generation of heat will drive the further volatilization of the remaining ethanol, thereby accelerating the polymerization time.
[0012] The invention provides a photon coating prepared by the above preparation method.
[0013] The film of the invention has high toughness and self-coloring properties, especially can quickly self-color under different humidity environments, and because of its good biocompatibility, can be used in the field of food packaging to detect whether food is damp.
[0014] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0015] (1) The mixed raw materials selected in the present invention are taken from nature, are green and environmentally friendly, and are degradable products, which have certain economy and practicality for the preparation, utilization and recycling of products;
[0016] (2) The photonic coating of the present invention can realize self-coloring characteristics and has high flexibility, which makes it have great application potential in the field of food packaging inspection;
[0017] (3) The present invention is a photonic coating, so the color appears during the coating production process. Compared with structural color film materials, the photonic coating of the present invention has unique advantages in constructing objects with different color shapes, and such colors will not fade due to changes in external shapes. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is an optical microscope image of the photonic coating prepared in Example 1, where a clear fingerprint texture can be observed;
[0019] Figure 2 This is an optical microscope image of the photonic coating prepared in Comparative Example 1, in which no photonic crystal characteristic texture can be observed;
[0020] Figure 3 The transmission spectra of the photonic coatings prepared in Examples 1-3 correspond to peak values in different visible light regions;
[0021] Figure 4 This is the transmission spectrum of the photonic coating prepared in Comparative Example 1, and no peak is observed in the visible light region.
[0022] Figure 5 The transmission spectra of the photonic coating prepared in Example 1 at 35% RH and 60% RH. Figure 5 It is shown that under similar humidity, the migration of the photon coating can cross the green and yellow light zones and finally reach the red light zone, proving its sensitivity to humidity (the entire migration process only takes 8 minutes). DETAILED DESCRIPTION
[0023] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.
[0024] The photonic coating prepared by the method of the present invention has higher flexibility than ordinary films, and can withstand folding times of more than 150 times (the folding time of ordinary films is less than 20 times); the photonic coating prepared by the method of the present invention has a fast response speed (it can complete self-coloration within 10 minutes under different humidity), better performance, better cyclic response performance, and has great potential in food packaging with internal humidity.
[0025] Example 1
[0026] A method for preparing a self-coloring bio-based photonic crystal coating comprises the following steps:
[0027] (1) The absolutely dry wood pulp was treated in 64% concentrated sulfuric acid at 50°C for 40 minutes, and then 10 times deionized water was added and mixed and allowed to stand for 10 hours. Then centrifugation was performed, and the acid solution of the first two room temperature centrifugal washings was replaced with deionized water, and the acid solution of the third and fourth centrifugal washings was replaced with 95%, at this time the centrifugal temperature was 5°C, and the final volume ratio of ethanol and water was controlled at 6:4, and the concentration of cellulose nanocrystals was 2.5wt%, which was stored in a refrigerator at 5°C.
[0028] (2) Add acrylamide, acrylic acid, methylenebisacrylamide and photoinitiator 2959 to the mixed solution obtained in step (1), wherein acrylamide and acrylic acid are mixed in a molar ratio of 3:1, and the amount of methylenebisacrylamide and photoinitiator 2959 added is 0.3% of the molar mass of acrylamide; the amount of the mixed solution of acrylamide, acrylic acid, methylenebisacrylamide and photoinitiator 2959 added is 20wt% of the mixed solution in step (1).
[0029] (3) 300 ml of the mixed solution obtained in step (2) was concentrated by rotary evaporation at 30° C. for 10 min to obtain a 4 wt % photonic coating containing acrylamide, acrylic acid, a crosslinking agent and a photoinitiator.
[0030] (4) 30 ml of the photonic coating obtained in step (3) was polymerized under 365 nm ultraviolet light for 20 min to obtain a photonic coating with high toughness and a blue color and a thickness of 90±5 μm.
[0031] Example 2
[0032] A method for preparing a self-coloring bio-based photonic crystal coating comprises the following steps:
[0033] (1) The absolutely dry wood pulp was treated in 64% concentrated sulfuric acid at 50°C for 40 minutes, and then 10 times deionized water was added and mixed and allowed to stand for 10 hours. Then centrifugation was performed, and the acid solution of the first two room temperature centrifugal washings was replaced with deionized water, and the acid solution of the third and fourth centrifugal washings was replaced with 95%, at this time the centrifugal temperature was 5°C, and the final volume ratio of ethanol and water was controlled at 5:5, and the concentration of cellulose nanocrystals was 2.8wt%, which was stored in a 5°C refrigerator.
[0034] (2) Add acrylamide, acrylic acid, methylenebisacrylamide and photoinitiator 2959 to the mixed solution obtained in step (1), wherein acrylamide and acrylic acid are mixed in a molar ratio of 3:1, and the amount of methylenebisacrylamide and photoinitiator 2959 added is 0.3% of the molar mass of acrylamide; the amount of acrylamide, acrylic acid, methylenebisacrylamide and photoinitiator 2959 added to the mixed solution is 30wt% of the mixed solution in step (1).
[0035] (3) 300 ml of the mixed solution obtained in step (2) was concentrated by rotary evaporation at 30° C. for 10 min to obtain a 6 wt % photonic coating containing acrylamide, acrylic acid, a crosslinking agent and a photoinitiator.
[0036] (4) 30 ml of the photonic coating obtained in step (3) was polymerized under 365 nm ultraviolet light for 20 min to obtain a photonic coating with a thickness of 100 ± 3 um and high toughness and a green color.
[0037] Example 3
[0038] A method for preparing a self-coloring bio-based photonic crystal coating comprises the following steps:
[0039] (1) The absolutely dry wood pulp was treated in 64% concentrated sulfuric acid at 50°C for 40 minutes, and then 10 times deionized water was added and mixed and allowed to stand for 10 hours. Then centrifugation was performed, and the acid solution of the first two room temperature centrifugal washings was replaced with deionized water, and the acid solution of the third and fourth centrifugal washings was replaced with 95%, at this time the centrifugal temperature was 5°C, and the final volume ratio of ethanol and water was controlled at 4:6, and the concentration of cellulose nanocrystals was 3wt%, which was stored in a refrigerator at 5°C.
[0040] (2) Add acrylamide, acrylic acid, methylenebisacrylamide and photoinitiator 2959 to the mixed solution obtained in step (1), wherein acrylamide and acrylic acid are mixed in a molar ratio of 4:1, and the added amount of methylenebisacrylamide and photoinitiator 2959 is 0.3% of the molar mass of acrylamide; the added amount of the mixed solution of acrylamide, acrylic acid, methylenebisacrylamide and photoinitiator 2959 is 30wt% of the mixed solution of step (1).
[0041] (3) 300 ml of the mixed solution obtained in step (2) was concentrated by rotary evaporation at 30° C. for 10 min to obtain a 5 wt % photonic coating containing acrylamide, acrylic acid, a crosslinking agent and a photoinitiator.
[0042] (4) 30 ml of the photonic coating obtained in step (3) was polymerized under 365 nm ultraviolet light for 20 min to obtain a photonic coating with high toughness and yellow color and a thickness of 110 ± 3 μm.
[0043] Comparative Example 1
[0044] The difference between this comparative example and Example 1 is that in step (1), the four centrifugations are all replaced with deionized water for washing, without using ethanol.
[0045] The results showed that the photon coating showed no color after photopolymerization, and its ultraviolet spectrum did not show a peak in the visible light region, further proving that it did not have the ability to display photon colors.
[0046] Comparative Example 2
[0047] The difference between this comparative example and Example 1 is that there is no step (2) (i.e., no acrylamide, acrylic acid, crosslinking agent and photoinitiator are added), that is, step (3) is directly performed after step (1) to concentrate by rotary evaporation to 4 wt %, and then dried at 30° C. to form.
[0048] The results show that its brittleness is much lower than that of Example 1, and the folding times of this comparative example are less than 30. The above embodiments are only preferred embodiments of the present invention, which are only used to explain the present invention, not to limit the present invention. Changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a self-coloring bio-based photonic crystal coating, characterized in that: The steps include: (1) preparing cellulose nanocrystals by a conventional sulfuric acid method: treating a raw material pulp with concentrated sulfuric acid, adding water to mix, standing, and then centrifuging to obtain a cellulose nanocrystal dispersion; the centrifugation means first centrifuging at room temperature and washing with water, and then centrifuging at low temperature and washing with an ethanol solution; the raw material pulp is wood pulp, cotton pulp, or straw pulp; the volume ratio of ethanol to water in the cellulose nanocrystal dispersion is (4-6):(6-4), and the concentration of cellulose nanocrystals in the cellulose nanocrystal dispersion is 2.5-3wt%; (2) mixing the cellulose nanocrystal dispersion with acrylamide, acrylic acid, a crosslinking agent and a photoinitiator to obtain a mixed solution; the molar ratio of acrylamide to acrylic acid is 3-4:1, and the amount of the crosslinking agent and the photoinitiator added is 0.2-0.4% of the molar amount of acrylamide; the amount of acrylamide, acrylic acid, crosslinking agent and photoinitiator added is 20-40wt% of the cellulose nanocrystal dispersion; (3) Concentrating the mixed solution obtained in step (2) to obtain a photonic coating; the concentration of the photonic coating is 4-8wt%; and the cross-linking agent is methylenebisacrylamide.
2. The method for preparing the self-coloring bio-based photonic crystal coating according to claim 1, characterized in that: The mass concentration of the concentrated sulfuric acid is 62-66%, and the concentrated sulfuric acid treatment condition is to treat the raw material slurry at 45-55° C. for 35-45 min; the added amount of the crosslinking agent and the photoinitiator is respectively 0.3% of the molar amount of acrylamide; the type of the photoinitiator is one or more of photoinitiator 651, photoinitiator TPO, and photoinitiator 2959.
3. The method for preparing the self-coloring bio-based photonic crystal coating according to claim 2, characterized in that: The concentrated sulfuric acid treatment condition is to treat the raw material slurry at 50° C. for 40 minutes; the photoinitiator is photoinitiator 2959.
4. The method for preparing the self-coloring bio-based photonic crystal coating according to claim 1, characterized in that: The raw material pulp is wood pulp; the concentration of the ethanol solution in the ethanol solution washing is 90-96%; the number of room temperature centrifugation and water washing is 1-3 times, and the number of low-temperature centrifugation and ethanol solution washing is 1-3 times; the low temperature is 2-8°C; the concentration in step (3) is rotary evaporation concentration, the temperature is 25-35°C, and the rotary evaporation time is 5-30min.
5. The method for preparing the self-coloring bio-based photonic crystal coating according to claim 4, characterized in that: The concentration of the ethanol solution in the ethanol solution washing is 95%; the number of room temperature centrifugation and water washing is 2 times, and the number of low temperature centrifugation and ethanol solution washing is 2 times.
6. A self-coloring bio-based photonic crystal coating obtained by the preparation method according to any one of claims 1 to 5.
7. A self-coloring bio-based photonic crystal coating, characterized in that: The bio-based photonic crystal coating is prepared by ultraviolet polymerization of the bio-based photonic crystal coating according to claim 6.
8. The self-coloring bio-based photonic crystal coating according to claim 7, characterized in that: The ultraviolet light polymerization is irradiated at 365nm, and the polymerization time is 20-30min; the thickness of the photon coating is 80-120um.
9. The use of the self-coloring bio-based photonic crystal coating according to claim 7, characterized in that: The self-chromic bio-based photonic crystal coating is used to detect humidity.
10. The use of the self-coloring bio-based photonic crystal coating according to claim 7, characterized in that: The self-coloring bio-based photonic crystal coating is used to detect whether food is damp in the field of food packaging.
Citation Information
Patent Citations
Self-color-changing bio-based photonic crystal coating as well as preparation and application thereof
CN116925584A